Uneventful days? A cautionary tale about the underestimated role of triggering events in employee silence research - Dominik Dilba; Bertolt Meyer (Journal of Occupational and Organizational Psychology, 2024)
Employee silence research stipulates that silence requires input to share, which we posit stems from encountering workplace events. We argue that the validity of relationships between employee silence and outcomes is limited without taking preceding events into account: Employees might not encounter relevant events and therefore cannot show silence. Further, workplace events can have independent effects on the outcomes attributed to silence, potentially confounding the effects of silence and preceding events. Drawing on an existing cross-cultural dataset ( N 0.167em=0.167em8222 in 35 samples), we show that some samples include up to 60% of participants who did not encounter relevant events. Using data from a German utility company ( N 0.167em=0.167em572 in 129 teams), we demonstrate that the associations between employee silence and outcomes like burnout are overestimated if effects of events are left unaccounted. Lastly, a simulation study shows that biased silence–outcome relations are generalizable whenever events have independent effects on the outcome of interest.
Keywords: 650; employee silence; event perspective; simulation study